Las dos caras de una ciudad: planificación y segregación urbana en el barrio de Monserrate - Grijalva Flores, Emil Faryd (Pontificia Universidad Católica del Perú, 2024)
This essay makes a critical analysis of the management of the Historic Center of Lima (CHL) through the Management of Planning, Management and Recovery of the Historic Center of Lima (PROLIMA) and its impact on urban segregation. It explores how policies focused on heritage conservation and tourism have led to an unequal distribution of attention and resources among the neighborhoods of the CHL, with special emphasis on the case of the Monserrate neighborhood. Despite its historical and cultural richness, Monserrate has been marginalized in terms of municipal investment and attention, resulting in significant deterioration of its infrastructure and high vulnerability to natural disasters. This essay reveals that PROLIMA’s interventions prioritize areas with greater tourism potential, leaving Monserrate and other similar neighborhoods in a state of neglect. This inaction is categorized as segregation by default, a perspective that explains how the deliberate or negligent omission of inclusive policies perpetuates the exclusion and marginalization of certain neighborhoods. The essay concludes that urban policies in Lima’s Historic Center have favored the restoration of monuments and cultural tourism, relegating neighborhoods such as Monserrate and perpetuating socio-spatial segregation. The effectiveness of the Master Plan for the Historic Center of Lima (PMCHL) is questioned due to the lack of citizen participation, which has disconnected urban policies from everyday realities. In addition, neighborhood resistance in Monserrate is highlighted as a response to municipal negligence and exclusion, highlighting the residential character that this area still possesses.

Este ensayo realiza un análisis crítico de la gestión del Centro Histórico de Lima (CHL) a través de la Gerencia de Planifi cación, Gestión y Recuperación del Centro Histórico de Lima (PROLIMA) y su impacto en la segregación urbana. Se explora cómo las políticas centradas en la conservación patrimonial y el turismo han provocado una distribución desigual de la atención y los recursos entre los barrios del CHL, poniendo especial énfasis en el caso del barrio Monserrate. A pesar de su riqueza histórica y cultural, Monserrate ha sido marginado en términos de inversión y atención municipal, lo que ha resultado en un signifi cativo deterioro de su infraestructura y una elevada vulnerabilidad a desastres naturales. Este ensayo revela que las intervenciones de PROLIMA priorizan las áreas con mayor potencial turístico, dejando a Monserrate y otros barrios similares en un estado de abandono. Esta inacción se cataloga como segregación por default, una perspectiva que explica cómo la omisión deliberada o negligente de políticas inclusivas perpetúa la exclusión y marginalización de ciertos barrios. El ensayo concluye que las políticas urbanas en el Centro Histórico de Lima han favorecido la restauración de monumentos y el turismo cultural, relegando barrios como Monserrate y perpetuando la segregación socioespacial. Se cuestiona la efi cacia del Plan Maestro del Centro Histórico de Lima (PMCHL) debido a la falta de participación ciudadana, lo que ha desconectado las políticas urbanas de las realidades cotidianas. Además, se destaca la resistencia vecinal en Monserrate como respuesta a la negligencia y exclusión municipal, resaltando el carácter residencial que aún posee esta zona.
The two faces of a city: Planning and urban segregation in the Monserrate neighborhood
Keywords: Segregation by default; Historical centers; Urban planning; Monserrate; Segregación por default; Centros históricos; Planificación urbana; Monserrate; https://purl.org/pe-repo/ocde/ford#5.04.01